Analisis Kesalahan Insya’ Pada Santri Kelas IV Pondok Pesantren Khadimul Ummah Bintan - aidillah suja (STAI Masjid Syuhada Yogyakarta, 2022)
The Boarding School tradition of mastering Arabic is one of the things that must be owned by every student, both oral and written. To achieve this, the Boarding School facilitates students with knowledge related to the Arabic language contained in the subjects, including: introduction to Arabic, Shorf, Nahwu, Insya’, Imla and so on. The subject is intended for students to achieve a proficiency which in terms of learning Arabic is called Al-Maharah Al-Arba'ah. Al-Maharah Al-Arba'ah. Based on the objectives of learning Arabic (Al-Maharah Al-Arba'ah) and its characteristics, both in terms of phonological, morphological, syntactic and semantic, Insya’ (writing essays) is one of the subjects that for some students is considered something difficult. This is because there are many differences between spoken and written language. Some of these fields can be classified into several of them: morphology, syntax, phonology, and semantics. Errors in language often occur in several aspects including: ignorance of language rules, imperfections in the application of language, and incorrect assumptions about language. these errors are very likely to occur in every foreign language or second language learner, therefore it is necessary to have an analysis of these language errors so that from the analysis you get information and knowledge about the mistakes that often occur, so that you don't fall back into mistakes. the same one.